Neotropical Meliponini: the genus Leurotrigona Moure two new species (Hymenoptera: Apidae, Apinae) - Pedro, Silvia R.m.; Camargo, João M.f. (Zootaxa, 2009)
Two new species of Leurotrigona are described: L. crispula sp. nov., from the Magdalena River valley, Antioquia, Colombia, and L. gracilis sp. nov., from western Amazon. Additional geographic records and illustrations are provided for L. muelleri (Friese) and L. pusilla Camargo & Moure, as well as an identification key to the species of the genus. Species can be recognized mainly by pilosity on the face. Morphological characters, including shape of the head and tibia III of the workers, and genitalia and pre-genital sterna of the male are indicative of two distinct groups, one composed of L. muelleri and L. gracilis sp. nov. and the other, of L. pusilla and L. crispula sp. nov.